THU0027 The Effect of Novel Compound Mcc950 on the Nlrp3 Inflammasome in the RA Joint. (9th June 2015) - McGarry, T.; Robertson, A.A.; Orr, C.; Coll, R.C.; Cooper, M.A.; O'Neill, L.A.; Veale, D.J.; Fearon, U.
Abstract : Background: The NLRP3 inflammasome is a multi-protein complex activated in response to environmental pathogens. These pathogens activate toll-like receptors, initiating a cascade leading to the activation of this inflammasome resulting in caspase-1-dependant cleavage of pro-IL-1β and IL-18 to their active and mature form. Recent studies have implicated the NLRP3 inflamamsome in the pathogenesis of Rheumatoid Arthritis. Objectives: To assess the activity of the NLRP3 inflammasome in the RA joint. Additionally, this study is the first to determine the effects of novel compound MCC950 in the RA joint. Methods: Initially, to assess if the NLRP3 inflammasome is active in RA, the expression of inflammasome components NLRP3, IL-1β, IL-18 and Caspase-1 were measured in Rheumatoid Arthritis (RA), Osteoarthritis (OA) and healthy control (HC) ex vivo synovial tissue biopsies by RT-PCR, ELISA, immunohistochemistry and Western blotting. The effects of MCC950, a novel compound targeting NLRP3, was assessed in macrophages derived from both HC peripheral blood mononuclear cells (PBMC) and THP1 cell line. The NLRP3 inflammasome was activated in these cells by incubation with LPS (1 μg/ml) and ATP (5 mM) in the presence or absence of MCC950 (10nM - 10μM), and secretion of NLRP3 inflammasome component IL-1β was measured by ELISA. RA synovial biopsies were also incubated with MCC950 (100 nM) or basal control for 24 hr and expression of NLRP3, IL-1β, IL-18 and Caspase-1 were analysed by Taqman PCR, ELISA and Western blotting. The effect of MCC950 on ex vivo pro-inflammatory and pro-angiogenic cytokine secretion (IL-6, IL-8, TNFα, VEGF, Tie-2, bFGF, MMP-3, IL-10) was also determined by multiplex ELISA. Results: Transcripts of inflammasome components NLRP3, pro-IL-1β and pro-IL-18 were significantly higher in RA versus OA synovial biopsies. Expression of Caspase-1 protein is also higher in RA versus OA synovial tissue as assessed by Western blotting. In addition, Caspase-1 is highly expressed in RA synovial tissue compared to OA or HC synovium, localised to the lining and sub-lining layers. MCC950 inhibits LPS and ATP induced secretion of inflammasome component IL-1β in macrophages derived from both HC PBMC and THP1 cells in a dose dependant manner. Furthermore, incubation of synovial ex vivo biopsies with MCC950 results in a decrease of NLRP3 transcripts, pro-IL1β and pro-IL-18, which was mirrored by a decrease in active IL-1β and IL-18 secreted from ex vivo RA biopsies (p<0.05). Caspase-1 expression was also inhibited in MCC950-treated ex vivo RA biopsies. Pro-inflammatory cytokines IL-6 and IL-8 were also significantly inhibited following incubation with MCC950. In contrast, MCC950 had no effect on other pro-inflammatory and pro-angiogenic factors TNFα, MMP-3, VEGF, Tie-2, bFGF and IL-10. Conclusions: MCC950, a novel compound thought to interact with the NLRP3 inflammasome, inhibits NLRP3 inflammasome components IL-1β, IL-18 and Caspase-1, in addition to other pro-inflammatory cytokines in the joint, but is independent of TNFα. This is the first study to demonstrate the effects of MCC950 in RA patient tissue and may represent a potential novel therapeutic strategy. Disclosure of Interest: T. McGarry: None declared, A. Robertson: None declared, C. Orr: None declared, R. Coll: None declared, M. Cooper: None declared, L. O'Neill: None declared, D. Veale Grant/research support from: Abvie, MSD, Pfizer, Roche, Consultant for: Pfizer, Roche, Speakers bureau: Abbott, MSD, Pfizer, Roche, U. Fearon: None declared